Growth, Biomass, Nutrient Storage and Crop Productivity under Different Tree Spacings of Gmelina arborea in Agrisilviculture System - Swamy, S.L.; Bharitya, J.K.; Mishra, Alka (Indian Journal of Agroforestry, 2020)
Variation in tree growth, above- and below-ground biomass and nutrient storage (N, P and K) in Gmelina arborea planted at three densities (4 x 4 m, 4 x 6 m and 4 x 8 m ) and their effect on productivity of wheat, linseed, mustard and urd crops were studied under agrislviculture system at Raipur (C.G.), India. After 5 years, total biomass ranged from 6.96 to 13.75 Mg ha-1. It was highest in trees planted under 4 x 4 m spacing and lowest in 4 x 8 m spacing. Stem wood accounted 58.4-59.7% to total biomass followed by roots (17.5-17.8%), branches (15.9-17.0%) and leaves (6.4-7.1%). In 5-year-old stands, total N ranged from 31.2 to 60.4 kg ha-1, P from 10.3 to 21.1 kg ha-1 and K from 24.3 to 47.5 kg ha-1. The yields of all crops decreased under G. arborea stands in comparison to their sole crops after 4 years of its planting. The yield losses were higher (13.16- 24.12%) in mustard and urd under close tree spacing (4 x 4 m), while it was lower (0.67 to 8.77%) in linseed and urd under wide tree spacing (4 x 8 m). Available nutrients in the soil were higher under 4 x 4 m tree spacing and decreased with soil depth. N, P and K in the soil had increased by 7.3%, 44.9% and 6.33%, respectively under this spacing (4 x4 m) compared to tree less control plot.